Determination of the Company's Cost of Production - Amiruddin, Amiruddin (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
This study aims to test and analyze the determination of the cost of production at CV. N Furniture Makassar. Data collection uses primary data obtained from the 2018 financial report CV. N Furniture Makassar. The results of these financial statements have been processed using the Full Costing method in seeing the determination of the cost of production of cabinets and chairs. Based on the research results prove that the determination of the cost of production at CV. N Furniture still uses the traditional system. Accounting treatment of damaged products in CV. N Furniture uses a method that is not in accordance with the existing theory, namely CV. N Furniture does not take into account the cost of damaged products because according to the company, damaged products are failed products and production costs for damaged products are charged to the finished product which is good.